Bezafibrate ameliorates diabetes via reduced steatosis and improved hepatic insulin sensitivity in diabetic TallyHo mice - Andras Franko; Susanne Neschen; Jan Rozman; Birgit Rathkolb; Michaela Aichler; Annette Feuchtinger; Laura Brachthäuser; Frauke Neff; Marketa Kovarova; Eckhard Wolf; Helmut Fuchs; Hans-Ulrich Häring; et al. (Elsevier, 2017)
Objective: Recently, we have shown that Bezafibrate (BEZ), the pan-PPAR (peroxisome proliferator-activated receptor) activator, ameliorated diabetes in insulin deficient streptozotocin treated diabetic mice. In order to study whether BEZ can also improve glucose metabolism in a mouse model for fatty liver and type 2 diabetes, the drug was applied to TallyHo mice. Methods: TallyHo mice were divided into an early (ED) and late (LD) diabetes progression group and both groups were treated with 0.5% BEZ (BEZ group) or standard diet (SD group) for 8 weeks. We analyzed plasma parameters, pancreatic beta-cell morphology, and mass as well as glucose metabolism of the BEZ-treated and control mice. Furthermore, liver fat content and composition as well as hepatic gluconeogenesis and mitochondrial mass were determined. Results: Plasma lipid and glucose levels were markedly reduced upon BEZ treatment, which was accompanied by elevated insulin sensitivity index as well as glucose tolerance, respectively. BEZ increased islet area in the pancreas. Furthermore, BEZ treatment improved energy expenditure and metabolic flexibility. In the liver, BEZ ameliorated steatosis, modified lipid composition and increased mitochondrial mass, which was accompanied by reduced hepatic gluconeogenesis. Conclusions: Our data showed that BEZ ameliorates diabetes probably via reduced steatosis, enhanced hepatic mitochondrial mass, improved metabolic flexibility and elevated hepatic insulin sensitivity in TallyHo mice, suggesting that BEZ treatment could be beneficial for patients with NAFLD and impaired glucose metabolism. Keywords: Bezafibrate, Glucose metabolism, Insulin resistance, Lipid metabolism, NAFLD